Design and fabrication of a 20 kilogram capacity cassava-based bioethanol distillation apparatus with 2.4 liter bioethanol output - Zuliantoro; Hidayat, Gunawan (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2024)
Background: The depletion of fossil fuel resources and growing environmental concerns have sparked interest in renewable energy sources like bioethanol. Cassava, an abundant crop in many tropical regions, shows promise as a feedstock for bioethanol production. This study aimed to design and fabricate an efficient small-scale distillation apparatus for producing bioethanol from cassava. Method: A distillation apparatus with 20 kg cassava capacity was designed and constructed using locally available materials. Key components included a distillation tank, condenser, cooling tower system, and burner. The apparatus was tested using fermented cassava mash to evaluate its performance in bioethanol production. Findings: The fabricated apparatus successfully produced 2.4 liters of bioethanol with 65% purity from 20 kg of cassava feedstock. Optimal distillation temperature was found to be 70°C, balancing ethanol yield and purity. Heat transfer calculations indicated 576 kW of cooling capacity was required in the condenser. The cooling tower system achieved 63% thermal efficiency. Conclusion: The designed distillation apparatus demonstrates the feasibility of small-scale bioethanol production from cassava. Further optimization of the distillation process and heat recovery systems could improve efficiency. This technology shows potential for decentralized biofuel production to meet local energy needs in cassava-producing regions. Novelty/Originality of this study: The study on designing small-scale distillation equipment for bioethanol production from cassava successfully demonstrated practical and affordable applications for decentralized biofuel production in cassava-producing areas.